2003
DOI: 10.1128/jvi.77.17.9439-9450.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Moloney Murine Leukemia Virus Repressor Binding Site Represses Expression in Murine and Human Hematopoietic Stem Cells

Abstract: The Moloney murine leukemia virus (MLV) repressor binding site (RBS) is a major determinant of restricted expression of MLV in undifferentiated mouse embryonic stem (ES) cells and mouse embryonal carcinoma (EC) lines. We show here that the RBS repressed expression when placed outside of its normal MLV genome context in a self-inactivating (SIN) lentiviral vector. In the lentiviral vector genome context, the RBS repressed expression of a modified MLV long terminal repeat (MNDU3) promoter, a simian virus 40 prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…To date, most studies of PBSmediated restriction have been performed in mouse cells. However, it has been reported that PBS Pro -mediated restriction also occurs in human cells (24). Thus it is likely that other mammals will also induce embryonic silencing of other PBS-containing retroviruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most studies of PBSmediated restriction have been performed in mouse cells. However, it has been reported that PBS Pro -mediated restriction also occurs in human cells (24). Thus it is likely that other mammals will also induce embryonic silencing of other PBS-containing retroviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work from many laboratories has documented the presence of strong sequence-specific DNA-binding activity for the PBS Pro of MLV in lysates of embryonic cells (9,12,13,24). Similar tests for DNA-binding activity in F9 EC cell extracts, when performed using the DNA sequence of PBS Lys-1,2 , the PBS used by retroviruses such as visna, spuma, and Mason-Pfizer monkey virus (20)(21)(22), yielded a complex detected by EMSA with a shift indicative of similar size as the complex that binds to the PBS Pro sequence (9) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been shown that repression of retroviral vectors containing the PBS-pro sequence is not restricted to ESCs and ECCs but is also evident in murine hematopoietic stem cells (Haas et al 2003) and ZFP809 expressing human embryonic kidney cells (Wolf and Goff 2009). Also, conditional KAP1 knockout in neural progenitor cells has recently been shown to result in ERV reactivation (Fasching et al 2015), indicating that ERV repression by KRAB-ZFPs and KAP1 plays a role in several somatic cell types.…”
Section: Discussionmentioning
confidence: 99%
“…9E) or MEFs at lower passages, when HDAC1 is predominantly localized to the nucleus, DNMT3L does not further influence the subcellular localization of HDAC1 significantly. The fact that HDAC1 is already localized to the nucleus in ES cells may account for their inherent ability to suppress retroviral activity (49,50). DNMT3L and TRIM28 synergistically silence proviral sequences in ES cells through multiple mechanisms.…”
Section: Discussionmentioning
confidence: 99%